The case of ihumatao: Interrogating competing corporate and indigenous visions of the future - Hancock, Frances; Lee-Morgan, Jenny; Newton, Pania; McCreanor, Tim (New Zealand Sociology, 2020)

Extractive industry, human rights and indigenous rights in New Zealand's exclusive economic zone - Erueti, Andrew; Pietras, Joshua (The New Zealand Yearbook of International Law, 2020)
This article is a response to the recent surge of interest over extractive industry in New Zealand and the opposition to this by many iwi. The New Zealand government has in recent years made offshore exploration and production a high priority. By the extractive industry, we mean the people, companies, and activities involved in removing oil and gas, metals, coal, stone and other useful resources from the ground.
Keywords: Aboriginal Australians–Civil rights; Discoveries in geography–Environmental aspects; Dispute resolution (Law); Economic zones (Law of the sea); Mineral industries–Economic aspects; Mineral industries–Government policy; New Zealand

Mana wahine: Decolonising gender in Aotearoa - Pihama, Leonie (Australian feminist studies, 2020)

'Maranga Ake Ai' the Heroics of Constitutionalising Te Tiriti O Waitangi/the Treaty of Waitangi in Aotearoa New Zealand - Ruru, Jacinta; Kohu-Morris, Jacobi (Federal Law Review, 2020)

River co-governance and co-management in Aotearoa New Zealand: enabling Indigenous ways of knowing and being - Fisher, Karen; Parsons, Meg (Transnational Environmental Law, 2020)

Introducing critical Tiriti policy analysis through a retrospective review of the New Zealand Primary Health Care Strategy - O’Sullivan, D; Came, Heather; McCreanor, T (Ethnicities, 2020)
BackgroundTe Tiriti o Waitangi was negotiated between the British Crown and Indigenous Māori leaders of Aotearoa New Zealand in 1840. Māori understood the agreement as an affirmation of political authority and a guarantee of British protection of their lands and resources. The Crown understood it as a cession of sovereignty. The tension remains, though legal and political developments in the last 35 years, have established that the agreement places a mandatory obligation on the Crown to protect and promote Māori health. It also requires that Māori may exercise rangatiratanga, or responsibility and authority, in relation to health policy development and implementation.MethodsTe Tiriti is, then, an instrument against which health policy is justly and efficaciously evaluated. This paper introduces critical Tiriti analysis as such an evaluative method. Critical Tiriti analysis involves reviewing policy documents against the Preamble and the Articles of te Tiriti o Waitangi. The review process has five defined phases: (i) orientation; (ii) close reading; (iii) determination; (iv) strengthening practice and (v) Māori final word.ResultsWe present a working example of critical Tiriti analysis using the New Zealand Government’s Primary Health Care Strategy published in 2001. This policy analysis found poor alignment with te Tiriti overall and the indicators of its implementation that we propose.ConclusionThis paper provides direction to policy makers wanting to improve Māori health outcomes and ensure Māori engagement, leadership and substantive authority in the policy process. It offers an approach to analysing policy that is simple to use and, inherently, a tool for advancing social justice.
Keywords: Critical Tiriti Analysis; Healthcare; Policy Analysis

The Waitangi Tribunal’s WAI 2575 Report - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Timothy (Health and Human Rights, 2020)
Te Tiriti o Waitangi, a treaty negotiated between Māori (the Indigenous peoples of Aotearoa) and the British Crown, affirmed Māori sovereignty and guaranteed the protection of hauora (health). The Waitangi Tribunal, established in 1975 to investigate alleged breaches of the agreement, released a major report in 2019 (registered as WAI 2575) about breaches of te Tiriti within the health sector in relation to primary care, legislation, and health policy. This article explores the implications of this report for the New Zealand health sector and the decolonial transformation of health systems. The tribunal found that the Crown has systematically contravened obligations under te Tiriti across the health sector. We complement the tribunal’s findings, through critical analysis, to make five substantive recommendations: (1) the adoption of Tiriti-compliant legislation and policy; (2) recognition of extant Māori political authority (tino rangatiratanga); (3) strengthening of accountability mechanisms; (4) investment in Māori health; and (5) embedding equity and anti-racism within the health sector. These recommendations are critical for upholding te Tiriti obligations. We see these requirements as making significant contributions to decolonizing health systems and policy in Aotearoa and thereby contributing to aspirations for health equity as a transformative concept.

Weaving mātauranga into environmental decision-making - Jones, Doug; Hikuroa, Dan; Gregory, Erica; Ihaka-McLeod, Hana; Moko-Mead, Te Taiawatea (New Zealand Science Review, 2020)
-
Keywords: environment; mātauranga māori

Ngā Whakaaro a Puhiwahine: A Political Philosophy and Theory from the Mōteatea of Puhiwahine - Simon, Hemopereki (2020)
Mōteatea are the orally sung literature and one of its most famous composers was Ngāti Tuwharetoa and Ngāti Maniapoto’s Puhiwahine. This paper will explore the political philosophy and theory contained within Puhiwahine’s waiata pakanga (war song) ‘Mā Wai Rā’ written for Ngāti Toa relations particularly their war leader, Te Rangihaeata. The observations from these forms of indigenous oral literature are based in a form of emerging indigenous philosophy called whakaaro based philosophy and method. Additionally, the author introduces a Kaupapa Māori Research method Marae ā-Rorohiko which outlines how social media, in particular Facebook, can be used as a form of group validity or qualitative data gathering. The analysis of the moteatea will focus on building a first person understanding of Māori philosophy and undestandings of mōteatea settler colonialism, colonisation and the centrality of mana and aroha in Māori society. It will reveal the that Puhiwahine had a deep understanding of Māori philosophy and what was to come from her people. It will also provide new understandings around the white possessive doctrine and mana motuhake.
Keywords: iwi politics; moteatea; pre-colonisation

Voting in Māori Governance Entities - Bargh, Maria; Rata, Arama (The International Indigenous Policy Journal, 2020)
Internationally, declining voter turnout is a topic of considerable concern in many liberal democracies. In this article, we investigate whether these similar trends can be discerned in the voter turnout for Māori governance entities. We first explore some of the demographic contexts within which Māori governance entities operate with a specific focus on population, residence, and age. We then provide a detailed descriptive analysis of voting data from one particular entity: Te Rūnanga o Ngāti Awa, with whom we worked to understand how their elections inform their aspirations for continuing connectedness with tribal members. In the final section of the article, we present findings from an analysis of publicly available tribal voting data to see whether the trend of declining voter turnout is observable and whether online voting is shown to impact turnout.
Keywords: iwi elections; kaupapa māori research; māori voting; online voting; post-settlement (waitangi tribunal); self-determination

The Misappropriation of the Haka: Are the Current Legal Protections Around Matauranga Maori in Aotearoa New Zealand Sufficient? - Wilson, Isabella Tekaumarua (Victoria University of Wellington Law Review, 2020)
Gale Academic OneFile includes THE MISAPPROPRIATION OF THE HAKA: ARE THE CURRENT LEGAL by Isabella Tekaumarua Wilson. Click to explore.
Keywords: intellectual property; kaitiakitanga; mātauranga māori; taonga; tiriti o waitangi/treaty of waitangi

Kia Tawharautia Te Matauranga Maori: Decolonising the Intellectual Property Regime in Aotearoa New Zealand - Kapa-Kingi, Eru (Victoria University of Wellington Law Review, 2020)
Gale Academic OneFile includes KIA TAWHARAUTIA TE MATAURANGA MAORI: DECOLONISING THE I by Eru Kapa-Kingi. Click to explore.
Keywords: decolonisation; intellectual property; mātauranga māori; tikanga | indigenous law; tino rangatiratanga; waitangi tribunal

Mātauranga Māori in geomorphology: existing frameworks, case studies, and recommendations for incorporating Indigenous knowledge in Earth science - Wilkinson, Clare; Hikuroa, Dan; Macfarlane, Angus; Hughes, Matthew (Earth Surface Dynamics, 2020)
Mixed-method bicultural research in Aotearoa New Zealand, including the weaving of Indigenous and other knowledge, is emerging within many academic disciplines. However, mātauranga Māori (the knowledge, culture, values, and world view of the Indigenous peoples of Aotearoa New Zealand) and Te Ao Māori (the Māori world) is poorly represented within geomorphological investigations. Here, we review international efforts to include Indigenous knowledge in geologic and geomorphic studies and provide an overview of the current state of mātauranga Māori within research endeavours in Aotearoa New Zealand. We review three theoretical frameworks (i.e. methodologies) for including mātauranga Māori in research projects and three models (i.e. methods) for including Māori values within research. We identify direct benefits to geomorphology and discuss how these frameworks and models can be adapted for use with Indigenous knowledge systems outside of Aotearoa New Zealand. The aim of this review is to encourage geomorphologists around the world to engage with local Indigenous peoples to develop new approaches to geomorphic research. In Aotearoa New Zealand, we hope to inspire geomorphologists to embark on research journeys in genuine partnership with Māori that promote toitū te mātauranga – the enduring protection, promotion and respect of mātauranga Māori.
Keywords: iwi governance; mātauranga māori; te ao Māori

Whānau, Tikanga and Tino Rangatiratanga: What is at stake in the debate over the Ministry for Children? - Fitzmaurice, Luke (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: crown policy; crown violence; discrimination; rangatiratanga; self-determination; tamariki; tikanga | indigenous law; waitangi tribunal

Seeing the unseen: evidence of kaupapa Māori health interventions - Rolleston, Anna K; Cassim, Shemana; Kidd, Jacquie; Lawrenson, Ross; Keenan, Rawiri; Hokowhitu, Brendan (AlterNative: An International Journal of Indigenous Peoples, 2020)
M?ori in Aotearoa have higher incidence, prevalence and mortality from chronic disease. The dominant narrative in Aotearoa about the reasons for M?ori ill health neglects to acknowledge the history of colonisation and failures of the health system, alongside the holistic view of health taken by M?ori focusing on collective, wh?nau-based outcomes. In this article, we review health interventions for chronic disease that have a kaupapa M?ori philosophical basis. Our findings demonstrate that there is no clear process in health service design, delivery, research and funding that values and understands m?tauranga M?ori. Western knowledge systems are inadequate for collecting and presenting M?ori knowledge. Overall, we highlight that the tension between acknowledging that a ?by M?ori, for M?ori? approach is best, and the difficulty in defining appropriate evidence collection methodology and outcome measures when funders and policy makers continue to require Western-centric interventions is an obstacle to improving M?ori health outcomes.
Keywords: health; health equity; kaupapa māori

Navigating towards marine co-management with Indigenous communities on-board the Waka-Taurua - Maxwell, Kimberley H.; Ratana, Kelly; Davies, Kathryn K.; Taiapa, Caine; Awatere, Shaun (Marine Policy, 2020)
Developing equitable marine management systems that recognise Indigenous worldviews, values, and practices, alongside international initiatives such as Ecosystem-Based Management (EBM) are paramount in countries which aim to recognise Indigenous rights. This is the case for New Zealand (NZ) where Indigenous-Māori rights to partner with the Government for the purpose of environmental management were guaranteed under the Treaty of Waitangi, 1840, and subsequent Acts (e.g. Resource Management Act, 1991). Our aim was to explore how both Indigenous-Māori and NZ societal values can be integrated into a marine co-management decision-making framework. Here we describe the Waka-Taurua (double-canoe) framework, and how it can be applied in developing a NZ marine management system (NZ-MMS), which includes both kaitiakitanga (a Māori concept of reciprocal care between Indigenous-Māori people and their territorial environment), and EBM, equitably. We argue that the Waka-Taurua framework can improve how marine co-management systems are developed by facilitating a more structured and equitable discussion of both Indigenous-Māori and broader societal worldviews, values, and practices.
Keywords: environmental management; governance; kaitiakitanga; kāwanatanga; water management

The Māori Electoral Option: How can trends in roll choices be explained? - Bargh, Maria (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
The Mäori Electoral Option is a period of 4 months, every 5 years, when Mäori electors can choose whether to be on the Mäori or the General Electoral Roll. The outcome of the Mäori Electoral Option is a key factor in determining the number of Mäori seats in the New Zealand Parliament. The Electoral Commission estimates that approximately 6,000 Mäori voters each year request to change electoral roll, but in 2017 over 19,000 voters applied to change. Why were so many more Mäori wanting to change and why did they not know they could only change during the Mäori Electoral Option held every 5 years? The following year, the 2018 Mäori Electoral Option saw the first net increase of Mäori changing to the general roll since 1996. This article uses data gathered from the results of Mäori Electoral Options 1991–2018, an anonymous survey, and evaluations of Mäori Electoral Option campaigns to consider how the shifting trends in roll choices might be explained.
Keywords: elections; kāwanatanga; māori electorates; māori seats; voting

Exploring the relationship between support for protest and psychological well-being for Māori - Houkamau, Carla A; Stronge, Samantha; Osborne, Danny; Sibley, Chris G; Dell, Kiri (New Zealand Journal of Psychology, 2020)
As a colonised peoples, many Māori have engaged in various forms of political resistance. Accordingly, research suggests that socio-political consciousness, which will sometimes involve at least considering protest, is an increasingly important aspect of identifying as Māori. This paper draws on a large, nationally representative sample of Māori (N = 1,977) to examine the links between expressing support for political activism (“activism” being used here synonymously with “protest”) and well-being. Support for political activism includes merely contemplating protesting and voting to support Māori issues, as well as actually signing petitions. Well-being includes selfreported mental health via the Kessler-6 and subjective health. Results show that support for political activism was strongly associated with greater subjective psychological distress and lower subjective health, above and beyond the variance explained by exhaustive demographic factors. This research presents the first empirical data in New Zealand demonstrating the strength of this relationship, and provides a good starting point for further investigation.
Keywords: activism; protest

'Pissed Off and Confused'/'Grateful and (Re)Moved': Affect, Privilege and National Commemoration in Aotearoa New Zealand - McConville, Alex; Wetherell, Margaret; McCreanor, Tim; Borell, Belinda; Moewaka Barnes, Helen (Political Psychology, 2020)
This article explores affect, colonial privilege, and the cultural politics of national commemoration in Aotearoa New Zealand. Based on focus‐group interviews around two major national days, we examine means through which feelings and emotions are deployed in ways that enable the reproduction of social advantage. Situating affect within patterns of relationship, four interrelated affective‐discursive practices are explored. In relation to Waitangi Day, agents tend to work under the rubric of anger and confusion. For Anzac Day, being grateful and moved shapes the interaction, although participants often indicate preferences towards "having a day off." Given the colonial context in which these practices circulate, analysis observes the associated freedom and ease by which affective‐discursive privilege is (re)produced. Often incongruent and rarely challenged, privilege allows associated actors to do what they want, when they want, however they want. This affective climate authorizes the ongoing reproduction of, and justification for, membership to a higher‐status ethnic group of which unearned opportunities and entitlements remain its everyday, expected currency.
Keywords: colonisation; memorialisation; national identity; white privilege

Beyond the veil: Kaupapa Māori gaze on the non-Māori subject - Borell, Belinda; Waru Rewiri, Kura Te; Moewaka Barnes, Helen; McCreanor, Tim (Journal of Sociology, 2020)
Kaupapa M?ori methodologies in Aotearoa New Zealand have often been applied to content of immediate and direct relevance to M?ori communities. Some of these include research about aspects of cultural revitalisation or examinations of the position M?ori occupy within broader ethnic disparities, particularly in health and social outcomes. This article seeks to expand the application of Kaupapa M?ori paradigms to research topics outside ?te ao Maori? (the M?ori world). We argue that the Kaupapa M?ori theorising of a M?ori visual arts and culture scholar can provide crucial insights on white privilege in Aotearoa New Zealand with a view to addressing disparities and creating more embracing and equitable perspectives of belonging, citizenship and nationhood.
Keywords: belonging; citizenship; identity; kaupapa māori

The relevance of Te Tiriti o Waitangi in the COVID-19 era - Charters, Claire (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; governance; rangatiratanga; tiriti o waitangi/treaty of waitangi

New normal - Same inequities or engaged Te Tiriti partnership? - Kukutai, Tahu; McIntosh, Tracey; Moewaka Barnes, Helen; McCreanor, Tim (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; mātauranga māori; tiriti o waitangi/treaty of waitangi; treaty partnership; treaty-based relationships

Same inequities or engaged te tiriti partnership? - Kukutai, T.; McIntosh, T.; Moewaka Barnes, H.; McCreanor, T. (MAI Journal, 2020)
Keywords: community; covid-19; treaty obligations

COVID-19 and the mass incarceration of Indigenous peoples - King, Paula; Cormack, Donna; Keenan, Rawiri (Journal of Indigenous Social Development, 2020)
Similar to experiences of Indigenous peoples globally, Māori in the nation-state known as New Zealand (NZ) have been subjected to mass incarceration by the colonial state. Places of detention are dangerous environments for the spread of COVID-19. We are deeply concerned about the potential for disproportionate impacts of COVID-19 on Māori and other Indigenous peoples within these environments as many have health conditions and/or multiple comorbidities compounding the risks of severe illness and death from COVID-19. We call for the NZ government to honour te Tiriti o Waitangi obligations and uphold Indigenous rights contained within the United Nations Declaration on the Rights of Indigenous Peoples and other international rights instruments. A whole-of-government commitment to an equitable public health approach is required to: 1) rapidly reduce the numbers of Māori in sites of detention; 2) implement effective, timely, evidenced informed measures to reduce the risk of COVID-19, in line with World Health Organization recommendations; 3) prevent the torture and cruel, inhuman or degrading treatment or punishment of detained Māori during COVID-19; and, 4) eliminate double-celling. Although focused on NZ, the themes we highlight are likely of relevance for Indigenous peoples across the globe in our collective resistance to the COVID-19 pandemic.
Keywords: UNDRIP; covid-19; incarceration; racism; tiriti o waitangi/treaty of waitangi; treaty obligations

Māori experiences of multiple forms of discrimination: findings from Te Kupenga 2013 - Cormack, Donna; Harris, Ricci; Stanley, James (Kōtuitui: New Zealand Journal of Social Sciences Online, 2020)
Comprehensive exploration of Māori experiences of discrimination in Aotearoa New Zealand remains limited, particularly in relation to exposure to multiple and interlocking forms of discrimination. This paper presents findings from a secondary analysis of Te Kupenga 2013, the first Māori Social Survey, examining patterning and prevalence of different forms of discrimination for Māori (n = 5,549). Māori report experiencing multiple forms of discrimination, both over their lifetimes and within the last year. Although racial discrimination was the most commonly reported form, Māori also experience discrimination on the basis of other grounds including age, gender, and income. Māori also report exposure to multiple forms of discrimination. Discrimination occurred in a range of settings, with schools and workplaces common sites. The findings support the lived reality of Māori that racial and other forms of discrimination are pervasive, and experienced in multiple domains across the life course, representing a persistent breach of rights. It is critical that other forms of discrimination are measured alongside racism in order to understand and address the realities of multiple discrimination for Māori in Aotearoa New Zealand.
Keywords: discrimination; racism; te kupenga; treaty obligations

Rights, interests and expectations: Indigenous perspectives on unrestricted access to genomic data - Hudson, Maui; Garrison, Nanibaa’ A.; Sterling, Rogena; Caron, Nadine R.; Fox, Keolu; Yracheta, Joseph; Anderson, Jane; Wilcox, Phil; Arbour, Laura; Brown, Alex; Taualii, Maile; Kukutai, Tahu; et al. (Nature Reviews Genetics, 2020)
Addressing Indigenous rights and interests in genetic resources has become increasingly challenging in an open science environment that promotes unrestricted access to genomic data. Although Indigenous experiences with genetic research have been shaped by a series of negative interactions, there is increasing recognition that equitable benefits can only be realized through greater participation of Indigenous communities. Issues of trust, accountability and equity underpin Indigenous critiques of genetic research and the sharing of genomic data. This Perspectives article highlights identified issues for Indigenous communities around the sharing of genomic data and suggests principles and actions that genomic researchers can adopt to recognize community rights and interests in data.
Keywords: crown law; data sovereignty; ethics; genes; genetic databases; genomic sequencing; population genetics